Politik Hukum Pembangunan Proyek Strategis Nasional di Pulau Lombok - Fauzan Hadi; Achmad Fadhil Fachryansyah (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
Legal politics is used as a basic reference for someone in determining values, determining and developing law. Law is a set of rules which regulate, both in terms of the order of life of the nation and state. The legal product is born democratically through an agreement from representatives of the people who work in the legislature. The political law of regional autonomy implementation according to Law number 23 of 2014. No matter how much autonomy is given to the regions, the final responsibility will remain with the government. The development carried out by the government must of course look at the RTRW, because it is the basic reference for the development project itself. The National Strategic Project (PSN) is a program implemented by the government itself or a business entity that has a strategic nature to provide and produce an equitable development impact in order to provide an increase in community welfare and regional development.